You are on page 1of 6

Homework #3

Course : Strength of Material


Name : Ni Kadek Sagit Ari Warsani
1. Show the following conjugate pair in shear stress in three-dimensional stress state.
𝜎12 = 𝜎21
𝜎13 = 𝜎31
𝜎23 = 𝜎32

Solution :

𝑑𝑥1 𝑑𝑥1 𝑑𝑥2 𝑑𝑥2


 −𝜎11 𝑑𝑥1 + 𝜎11 𝑑𝑥1 −𝜎22 +𝜎22
3 3 3 3

−𝜎12 𝑑𝑥2 𝑑𝑥1 +𝜎21 𝑑𝑥1 𝑑𝑥2 =0


−𝜎12+𝜎21 =0
−𝜎12=−𝜎21
 𝜎12 = 𝜎21
𝑑𝑥1 𝑑𝑥1 𝑑𝑥3 𝑑𝑥3
 −𝜎11 𝑑𝑥1 + 𝜎11 𝑑𝑥1 −𝜎33 +𝜎22
3 3 3 3

−𝜎13 𝑑𝑥3 𝑑𝑥1 +𝜎31 𝑑𝑥1 𝑑𝑥3 =0


−𝜎13+𝜎31 =0
−𝜎13=−𝜎31
 𝜎13 = 𝜎31
𝑑𝑥2 𝑑𝑥2 𝑑𝑥3 𝑑𝑥3
 −𝜎22 𝑑𝑥2 + 𝜎22 𝑑𝑥2 −𝜎33 +𝜎22
3 3 3 3

−𝜎23 𝑑𝑥3 𝑑𝑥2 +𝜎32 𝑑𝑥2 𝑑𝑥3 =0


−𝜎23+𝜎32 =0
−𝜎23=−𝜎32
 𝜎23 = 𝜎32

2. Show the following equations by using theorems of trigonometric function.


1 1
𝜎11 𝑐𝑜𝑠 2 𝜃 + 𝜎22 𝑠𝑖𝑛2 𝜃+2𝜎12 𝑐𝑜𝑠𝜃𝑠𝑖𝑛𝜃 = 2 (𝜎11 + 𝜎22 ) + 2 (𝜎11 − 𝜎22 )𝑐𝑜𝑠2𝜃 + 𝜎12 𝑠𝑖𝑛2𝜃
1
(−𝜎11 + 𝜎22 )𝑐𝑜𝑠𝜃𝑠𝑖𝑛𝜃 + 𝜎12(𝑐𝑜𝑠 2 𝜃 − 𝑠𝑖𝑛2 𝜃) = (−𝜎11 + 𝜎22 )𝑠𝑖𝑛2𝜃 + 𝜎12 𝑐𝑜𝑠2𝜃
2

Theorems of trigonometric function are follows.


𝑠𝑖𝑛2 𝜃 + 𝑐𝑜𝑠 2 𝜃 =1 (1)
𝑐𝑜𝑠 2 𝜃 − 𝑠𝑖𝑛2 𝜃 = 𝑐𝑜𝑠2𝜃 (2)
1
𝑐𝑜𝑠 2 𝜃 = 2 (𝑐𝑜𝑠2𝜃 +1) (3)

𝑠𝑖𝑛𝜃𝑐𝑜𝑠𝜃 = 𝑠𝑖𝑛2𝜃 (4)


𝒔𝒐𝒍𝒖𝒕𝒊𝒐𝒏.
By using the Eqs. (1) and (3), we find
𝜎11 𝑐𝑜𝑠 2 𝜃 + 𝜎22 𝑠𝑖𝑛2 𝜃 = 𝜎11 𝑐𝑜𝑠 2 𝜃 + 𝜎22 (1 − 𝑐𝑜𝑠 2 𝜃)
= 𝜎22 + (𝜎11 − 𝜎22 )𝑐𝑜𝑠 2 𝜃
1
= 𝜎22 + (𝜎11 − 𝜎22 )(𝑐𝑜𝑠2𝜃 + 1)
2
1 1
= 2 (𝜎11 + 𝜎22 )+2 (𝜎11 − 𝜎22 ) 𝑐𝑜𝑠2𝜃

By using Eq.(4), we find


2𝜎12 𝑐𝑜𝑠𝜃𝑠𝑖𝑛𝜃 = 𝑠𝑖𝑛2𝜃
1
(−𝜎11 + 𝜎22 )𝑐𝑜𝑠𝜃𝑠𝑖𝑛𝜃 = (−𝜎11 + 𝜎22 ) 𝑠𝑖𝑛2𝜃
2
By using Eq.(2), we find
𝜎12 (𝑐𝑜𝑠 2 𝜃 − 𝑠𝑖𝑛2 𝜃) = 𝜎12 𝑐𝑜𝑠2𝜃
From this equation, we deduce the first equation.
3. Show the following equation by using Theorems of trigonometric function.
𝜎 = 𝐶 + 𝑅𝑐𝑜𝑠(2𝜃 − 2𝜙)
𝜏 = 𝑅𝑠𝑖𝑛(2𝜃 − 2𝜙)
2𝜎12
Where tan2𝜙= 𝜎
11 −𝜎22

Theorems of trigonometric function are follows.


𝑎 cos 𝜃 + 𝑏 sin 𝜃 = √𝑎2 − 𝑏 2 cos (𝜃 − 𝜙)

−𝑎 sin 𝜃 + 𝑏 cos 𝜃 = √𝑎2 − 𝑏 2 sin (𝜃 − 𝜙)


𝑏
Where tan 𝜙 = 𝑎

Solution.
From no.2 and above theorems, we find
1 1
𝜎 = 2 (𝜎11 + 𝜎22 ) + 2 (−𝜎11 + 𝜎22 )
1
𝜏= (−𝜎11 + 𝜎22 )𝑠𝑖𝑛2𝜃 + 𝜎12 𝑐𝑜𝑠2𝜃
2
𝜏 = 𝑅𝑠𝑖𝑛(2𝜃 − 2𝜙)
Homework #3
Course : Strength of Material
Name : I Putu Abdi Karya
1. Show the following conjugate pair in shear stress in three-dimensional stress state.
𝜎12 = 𝜎21
𝜎13 = 𝜎31
𝜎23 = 𝜎32

Solution :

𝑑𝑥1 𝑑𝑥1 𝑑𝑥2 𝑑𝑥2


 −𝜎11 𝑑𝑥1 + 𝜎11 𝑑𝑥1 −𝜎22 +𝜎22
3 3 3 3

−𝜎12 𝑑𝑥2 𝑑𝑥1 +𝜎21 𝑑𝑥1 𝑑𝑥2 =0


−𝜎12+𝜎21 =0
−𝜎12=−𝜎21
 𝜎12 = 𝜎21
𝑑𝑥1 𝑑𝑥1 𝑑𝑥3 𝑑𝑥3
 −𝜎11 𝑑𝑥1 + 𝜎11 𝑑𝑥1 −𝜎33 +𝜎22
3 3 3 3

−𝜎13 𝑑𝑥3 𝑑𝑥1 +𝜎31 𝑑𝑥1 𝑑𝑥3 =0


−𝜎13+𝜎31 =0
−𝜎13=−𝜎31
 𝜎13 = 𝜎31
𝑑𝑥2 𝑑𝑥2 𝑑𝑥3 𝑑𝑥3
 −𝜎22 𝑑𝑥2 + 𝜎22 𝑑𝑥2 −𝜎33 +𝜎22
3 3 3 3

−𝜎23 𝑑𝑥3 𝑑𝑥2 +𝜎32 𝑑𝑥2 𝑑𝑥3 =0


−𝜎23+𝜎32 =0
−𝜎23=−𝜎32
 𝜎23 = 𝜎32

2. Show the following equations by using theorems of trigonometric function.


1 1
𝜎11 𝑐𝑜𝑠 2 𝜃 + 𝜎22 𝑠𝑖𝑛2 𝜃+2𝜎12 𝑐𝑜𝑠𝜃𝑠𝑖𝑛𝜃 = 2 (𝜎11 + 𝜎22 ) + 2 (𝜎11 − 𝜎22 )𝑐𝑜𝑠2𝜃 + 𝜎12 𝑠𝑖𝑛2𝜃
1
(−𝜎11 + 𝜎22 )𝑐𝑜𝑠𝜃𝑠𝑖𝑛𝜃 + 𝜎12(𝑐𝑜𝑠 2 𝜃 − 𝑠𝑖𝑛2 𝜃) = (−𝜎11 + 𝜎22 )𝑠𝑖𝑛2𝜃 + 𝜎12 𝑐𝑜𝑠2𝜃
2

Theorems of trigonometric function are follows.


𝑠𝑖𝑛2 𝜃 + 𝑐𝑜𝑠 2 𝜃 =1 (1)
𝑐𝑜𝑠 2 𝜃 − 𝑠𝑖𝑛2 𝜃 = 𝑐𝑜𝑠2𝜃 (2)
1
𝑐𝑜𝑠 2 𝜃 = 2 (𝑐𝑜𝑠2𝜃 +1) (3)

𝑠𝑖𝑛𝜃𝑐𝑜𝑠𝜃 = 𝑠𝑖𝑛2𝜃 (4)


𝒔𝒐𝒍𝒖𝒕𝒊𝒐𝒏.
By using the Eqs. (1) and (3), we find
𝜎11 𝑐𝑜𝑠 2 𝜃 + 𝜎22 𝑠𝑖𝑛2 𝜃 = 𝜎11 𝑐𝑜𝑠 2 𝜃 + 𝜎22 (1 − 𝑐𝑜𝑠 2 𝜃)
= 𝜎22 + (𝜎11 − 𝜎22 )𝑐𝑜𝑠 2 𝜃
1
= 𝜎22 + (𝜎11 − 𝜎22 )(𝑐𝑜𝑠2𝜃 + 1)
2
1 1
= 2 (𝜎11 + 𝜎22 )+2 (𝜎11 − 𝜎22 ) 𝑐𝑜𝑠2𝜃

By using Eq.(4), we find


2𝜎12 𝑐𝑜𝑠𝜃𝑠𝑖𝑛𝜃 = 𝑠𝑖𝑛2𝜃
1
(−𝜎11 + 𝜎22 )𝑐𝑜𝑠𝜃𝑠𝑖𝑛𝜃 = (−𝜎11 + 𝜎22 ) 𝑠𝑖𝑛2𝜃
2
By using Eq.(2), we find
𝜎12 (𝑐𝑜𝑠 2 𝜃 − 𝑠𝑖𝑛2 𝜃) = 𝜎12 𝑐𝑜𝑠2𝜃
From this equation, we deduce the first equation.
3. Show the following equation by using Theorems of trigonometric function.
𝜎 = 𝐶 + 𝑅𝑐𝑜𝑠(2𝜃 − 2𝜙)
𝜏 = 𝑅𝑠𝑖𝑛(2𝜃 − 2𝜙)
2𝜎12
Where tan2𝜙= 𝜎
11 −𝜎22

Theorems of trigonometric function are follows.


𝑎 cos 𝜃 + 𝑏 sin 𝜃 = √𝑎2 − 𝑏 2 cos (𝜃 − 𝜙)

−𝑎 sin 𝜃 + 𝑏 cos 𝜃 = √𝑎2 − 𝑏 2 sin (𝜃 − 𝜙)


𝑏
Where tan 𝜙 = 𝑎

Solution.
From no.2 and above theorems, we find
1 1
𝜎 = 2 (𝜎11 + 𝜎22 ) + 2 (−𝜎11 + 𝜎22 )
1
𝜏= (−𝜎11 + 𝜎22 )𝑠𝑖𝑛2𝜃 + 𝜎12 𝑐𝑜𝑠2𝜃
2
𝜏 = 𝑅𝑠𝑖𝑛(2𝜃 − 2𝜙)